The Structural Relationship of Treatment Adherence Based on Illness Perception in Patients with Psoriasis: The Mediating Role of Body Image Concern - Yousefi, Amir; Jalali, Mohsen; Badelleh Shamshuki, MohammadTaghi; Azizi Ziabari, LeilaSadat (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study examines the structural relationship of treatment adherence based on illness perception in patients with psoriasis, considering the mediating role of body image concern. Methodology: This study employs a descriptive-correlational research method based on structural modeling. The statistical population consists of patients with psoriasis in Tehran. Based on the inclusion and exclusion criteria, 250 patients with psoriasis will be selected using a purposive convenience sampling method. The data collection tools include the Ziaei Treatment Adherence Questionnaire (2009), the Littleton Body Image Concern Inventory (2005), and the Broadbent et al. Illness Perception Questionnaire (2006). Data analysis is conducted using structural regression equation modeling. The collected data are analyzed using SPSS 18 and AMOS 23 software. Findings: The findings indicate that illness perception has a direct effect on treatment adherence in individuals with psoriasis. Additionally, body image concern has a direct effect on treatment adherence in these patients. Moreover, illness perception indirectly affects treatment adherence through the mediating role of body image concern. Conclusion: Thus, addressing psychological and social factors can enhance adherence, improving treatment outcomes and patients’ quality of life.